Adaptive Control Solution for a Class of MIMO Uncertain Underactuated Systems with Saturating Inputs - Kulkarni, Ajay; Kumar, Abhay (International Journal of Intelligent Systems and Applications in Engineering, 2016)
This paper addresses the issue of controller design for aclass of multi-input multi-output (MIMO) uncertain underactuatedsystems with saturating inputs. A systematic controller framework,composed of a hierarchically generated control term, meant toensure the stabilization of a particular portion of system dynamicsand some dedicated control terms designed to solve the trackingproblem of the remaining system dynamics is presented. Waveletneural networks are used as adaptive tuners to approximate thesystem uncertainties also to reshape the control terms so as to dealwith the saturation nonlinearity in an antiwindup paradigm.Gradient based tuning laws are developed for the online tuning ofadjustable parameters of the wavelet network. A Lyapunov basedstability analysis is carried out to ensure the uniformly ultimatelybounded (UUB) stability of the closed loop system. Finally, asimulation is carried out which supports the theoreticaldevelopment.